Effect of matrix metalloproteinase 8 inhibitor and chlorhexidine on the cytotoxicity, oxidative stress and cytokine level of MDPC-23. Issue 11 (November 2018) - Ou, Qianmin; Tan, Lingping; Huang, Xiaojun; Luo, Qipei; Wang, Yan; Lin, Xuefeng
Highlights: The cytotoxicity of CHX was dose and time dependent, while MMP8-I (0–500 μM) had no obvious cytotoxicity until the concentration of 1000 μM. The treatment of MMP8-I did not cause the obvious oxidative stress and cell apoptosis on MDPC-23. Comparing with CHX, MMP8-I had not caused the obvious disorder of immune response. Abstract: Objective: This study investigated the effect of matrix metalloproteinase-8 inhibitor I (MMP8-I) and chlorhexidine (CHX) on the viability, oxidative stress and cytokine secretion of MDPC-23 under short-term (30 min) and long-term (3 days) culture. Methods: MDPC-23 were treated with MMP8-I or CHX for 30 min, 1 day, 2 days and 3 days to detect the proliferation by 3-[4, 5-dimethylthiazol-2-yl]-2, 5 diphenyl tetrazolium bromide (MTT) assay. In the following assays, MDPC-23 treated with 0.0003% CHX were referred to CHX group, treated with 8 μM MMP8-I were MMP8-I group. Cells without additional treatment were regarded as control group. The cell cycle, reactive oxygen species (ROS) level, and apoptosis were assessed by flow cytometry. The cytokine level was quantified by enzyme-linked immunosorbent assay (ELISA). Results: In 30 min, CHX at concentrations higher than 0.0003% dilution inhibited cell proliferation when compared to the control group. MMP8-I (0.1–500 μM) showed no obvious cytotoxicity to MDPC-23, and MMP8-I (1000 μM) inhibited cell proliferation. In 3 days, CHX (0.0003%) significantly inhibited cell growth, while MMP8-I (8 μM) had no cytotoxicity. In the CHX group, the S phase population was decreased, and cellular ROS were increased in 3 days. In the MMP8-I group, the change of S phase population and cellular ROS was not significant compared with the control group. Cell apoptosis was not elevated in the MMP8-I group, while the apoptosis rate was increased in the CHX group both in 30 min and 3 days. In 30 min, CHX treatment significantly increased the secretion of interleukin (IL)-1β and IL-8, but slightly increased the secretion of IL-10, while MMP8-I caused no change in cytokines. In 3 days, CHX treatment significantly increased the secretion of IL-1β, IL-6, and IL-8, and inhibited the secretion of IL-10. MMP8-I treatment caused the increase of IL-6. Significance: Compared with CHX, MMP8-I at low concentration did not result in cytotoxicity, oxidative stress, or the disorder of immune response.